Clinical behavior - ethiologic of the syncope in patient pediatric - Amarales, Dra. Idalia Morell; Rodríguez, MCs. Dalyla Alonso; Cuesta, MCs. Niurka González (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
the syncope constitutes a complex problem that requires of a clinical guide that he/she rationalizes it. In the last years it is bigger the interest for the handling of different causes due to their frequency, nature incapacitante, their potential graveness and to the complex problems implied in their genesis and difficult to diagnose. He/she was carried out a study in 80 patients assisted in the external consultation of cardiology, of the Policlínic of Pediatric Specialties, and coming from the area of hospitalization. the prematuried antecedent is not picked up as factor to predispose you in the revised literature and this could keep relationship with the síncope. In relationship to the cianosis this aspect it was not significant, the same as the apnea crises and the ventilation mechanics in the stage neonatal, however the antecedent of infections was outstanding following him the hipoxia, the first floor weight when being born and the slowed intra-uterine growth. A bigger incidence of the syncope is reported in patient with relatives that suffer of arterial hypertension. The sudden death in spite of constituting a factor to predispose you very important, it reports few cases since in this study they are not frequent such cases. He/she was a bigger factors begined like the fear, the pain and the maintained stress, this last one mainly in the adolescents. Most of the patients presented syncopes of vasovagal etiology. Other less frequent causes those of origin psicogen, neurological, heart, endocrine and by drugs. the glucemia levels and hemoglobin in most of the cases stayed in their normal values.